Imaging anatomy. text and atlas. Volume 1, Lungs, mediastinum, and heart - Saremi, Farhood (New York : Thieme, 2021)
"This atlas provides high-quality multiplanar and volumetric color-coded imaging techniques utilizing CT, MRI, or angiography, supplemented by cadaveric presentations and color drawings that best elucidate each specific anatomic region. Twenty-one chapters with concise text encompass thoracic wall, mediastinum, lung, vascular, and cardiac anatomy, providing readers with a virtual dissection experience. Many anatomical variants along with pathological examples are presented"--
Thoracic Wall -- Tracheobronchial System -- Mediastinum and Thymus -- Lungs -- The Pleura -- Pulmonary Artery and Vein -- Pulmonary and Systemic Veins -- Thoracic Aorta and Major Branches -- Lymphatics and Nerves of the Thorax -- Diaphragm -- Breast Anatomy -- General Anatomy of the Heart -- Atrioventricular Septal Region -- The Aortic Valve -- Pulmonary Valve -- The Mitral Valve -- The Tricuspid Valve Apparatus -- Coronary Arteries and Myocardial Perfusion -- The Coronary Veins -- The Pericardium
Includes bibliographical references and index
Online resource; title from digital title page (viewed on January 13, 2022).
eBooks on EBSCOhost
Keywords: Diagnostic imaging -- Atlases; Lungs -- Anatomy -- Atlases; Mediastinum -- Anatomy -- Atlases; Heart -- Anatomy -- Atlases; Lung -- anatomy & histology; Lung -- diagnostic imaging; Mediastinum -- anatomy & histology; Mediastinum -- diagnostic imaging; Heart -- anatomy & histology; Heart -- diagnostic imaging; Diagnostic Imaging -- methods; Imagerie pour le diagnostic -- Atlas; Poumons -- Anatomie -- Atlas; Médiastin -- Anatomie -- Atlas; Cœur -- Anatomie -- Atlas; Diagnostic imaging; Heart; Lungs; Mediastinum; Atlas; atlases; Scientific atlases; Atlases; Anatomical atlases; Atlases; Atlas